Penyelesaian Masalah Gadai Syariah (Rahn) Pada Pegadaian Syariah - Ramadan, La Ode Alfachriy Ridla; Latupono, Barzah; Fataruba, Sabri (Pusat Kajian Hukum Bisnis Fakultas Hukum Universitas Pattimura, 2025)
Pawning is a means for the wider community to borrow money by handing over valuables as collateral. Resolving sharia pawn problems (rahn) is an integral part that prioritizes the principles of justice, responsibility and compliance with Islamic law. However, during the implementation of transactions, legal problems often arise which cause losses for customers. The purpose of this research is to find out and explain the application of sharia principles to rahn contracts, and to find out and explain the steps to resolve rahn contract problems when disputes occur, such as customers whose collateral is exchanged for fake gold and the responsibility of the pawnshop for collateral items that have been exchanged. . The research method used is normative juridical research with a descriptive analytical research type using a conceptual approach and a statutory regulatory approach. The research results show that the application of sharia principles in resolving rahn contract problems cannot be separated from the role of the National Sharia Council (DSN) which is tasked with developing the application of sharia values ​​in economic activities as well as steps to resolve rahn contract problems when experiencing disputes in the form of loss of collateral. Replaced by the pawnshop in accordance with Financial Services Authority Regulation Number 31 of 2016 concerning Pawnshop Business.